Novel anti reflux bariatric surgery: laparoscopic revision of gastric band to Nissen fundoplication and sleeve gastrectomy - Pok, E.H.; Lee, W.J. (2014)
In this video we present the case of a 32-year old lady without co-morbidity (BMI 35kg/m2) presented with severe gastro-oesophageal reflux (GERD) having previously undergone an laparoscopic gastric banding in 2011 (original BMI 34kg/m2) to aid weight loss. The barium swallow demonstrated impaired motility in the entire oesophagus with gastro-oesophageal reflux to the level of the mid-oesophagus. Although Roux-en-Y gastric bypass would be an ideal revisional procedure for GERD but she considered it was too drastic procedure for weight loss with risk of long term complications. Therefore, a novel anti-reflux sleeve gastrectomy with combination of Nissen fundoplication and sleeve gastrectomy was undertaken. The patient made an uncomplicated recovery and was discharged on postoperative day 3 with ameliorated reflux symptoms. At 4 months, her BMI was 29.7 kg/m2 and EWL 19.6% with completely resolved GERD.